Posttraumatic growth in pediatric intensive care personnel and its dependence on resilience and coping strategies. - Rodríguez Rey, Rocio; Palacios, Alba; Alonso Tapia, Jesús; Pérez, Elena; Álvarez, Elena; Coca, Ana; Mencía, Santiago; Marcos, Ana; Mayordomo Colunga, Juan; Fernández, Francisco; Gómez, Fernando; Cruz, Jaime; et al. (My University)
Este trabajo estudia a) los niveles de crecimiento postraumático en personal de UCI pediátrica, y si estos niveles son distintos en profesionales que trabajan en otras unidades pediátricas, b) el papel de la resiliencia y las estrategias de afrontamiento en la predicción de los niveles de crecimiento, y c) la relación entre variables demográficas y laborales con los niveles de crecimiento postraumático.

OBJECTIVE: Staff in pediatric intensive care units (PICU) are inherently exposed to potentially traumatic events. Posttraumatic growth (PTG) is the occurrence of positive changes after experiencing a traumatic event. This study aims (a) to evaluate the prevalence of PTG in PICU staff, and whether their scores are different from those reported by professionals working in other pediatric units, (b) to explore the role of resilience and coping strategies in predicting PTG, and (c) to explore the relation of demographic and work-related variables with PTG. METHOD: Participants of this multicentric, cross sectional study were 298 PICU workers and 189 professionals working in noncritical pediatric units. They completed the Brief Resilience Scale, a Coping Strategies Questionnaire, the Posttraumatic Growth Inventory (PTGI), and provided demographic and work-related information. RESULTS: Of PICU staff, 68.8% experienced growth to a "great" or "very great" degree in at least one of the PTGI's dimensions. Higher PTG was reported following the death of a child or after a recent conflict with a work colleague. PICU workers and noncritical pediatric staff showed equivalent PTG levels. Multigroup path analysis with latent variables showed that emotion-focused coping was related to PTG only in PICU staff, whereas problem-focused coping was related to PTG in both groups. The relation between resilience and PTG was not significant. CONCLUSIONS: Work-related trauma can act as a catalyst for positive posttrauma changes. Modifying coping strategies may be a way to foster PTG in health care providers.
Artículos en revistas